Atrial Flutter with 1:1 Atrioventricular Conduction (London Journal of Medical and Health Research, 2025)
Introduction: Generally, atrial flutter leads 2:1 to the ventricles. It rarely leads 1:1, with states of cardiogenic shock. Due to the very fast ventricular rate.Objetives: To present patients with atrial flutter, with 1:1 atrioventricular conduction. Explain diagnostic methods. Review production mechanisms. Define the causes of presentation in exposed. patients. Mention the behavior and treatment.Methods: The following were taken in to account: Electrocardiogram with heart rate greater tan Identification of atrial flutter waves. Determination of 1:1 atrioventicular conduction. Typing of heart disease. Evaluation of hemodynamic status. Age and sex. Then we proceded to treatment and behavior.Results: Ten patients were observed. Average age 57 (22-72). Ischemic heart disease 4; chronic rheumatic 2; chronic cor pulmonale 2; dilated cardiomyopathy 1 and pre-excitation syndrome 1. Average atrial rate 257 (240-270). Hemodynamic instablity 6. Treatment: electrical cardioversin 5; Amiodarone 2; Digoxin 1; descontinuation of Digoxin 1 and spontaneous 1. Vagal maneuver was performed in 5. Digoxin precipitated the arrhythmia in 1,in the rest it was triggered spontaneously.Conclusion: The mayority of cases had heart disease. The arrhythmia can be confused with ventricular tachycardia and paroxismal supraventricular tachycardia. Vagal maneuvers help in the diagnosis. Depending on the state of hemodynamic stability, it card be treated with antiarrhythmics or electrical cardioversin.
Keywords: urogenital abnormality; anorectal malformation; Creatinine; Electrolytes; Urea.; Biochemical parameters; dengue patients; serum albumin; serum ALT; Indigenous Knowledge; traditional medicine (tm); herbs; nso; bakweri; efficacy; inefficacy; traditional healers; herbal remedies; medical anthropology.; Arrhythmia; Atrial flutter; Vagal maneuvers; Electrical cardioversi